Determination of packet priority by genetic algorithm in the packet switching networks - Tuncer, T; Karci, A (Springer-Verlag Berlin, 2004)
The packet with small size waits too much time in the packet switching network, while a packet with large size is being served at current time in FIFO strategy. The starvation for packet with large size is exist in the packet switching network in packet size strategy while there is always at least one packet with small size being served or queued in the network. In this study, a method based on the GA exploiting the advantages of FIFO and packet size strategies and removing disadvantages of both methods will be presented. The packet sequence is determined by the proposed method. At this aim, four parameters (the order of packet incoming in to queue, packet size, waiting time in the queue and TTL) were used.
8th International Conference on Knowledge-Based Intelligent Information and Engineering Systems -- SEP, 2004 -- Wellington Inst Technol, Wellington, NEW ZEALAND
Keywords: packet priority; genetic algorithms; packet switching network